An audit of obstetric admissions to intensive care unit in a medical college hospital of central India: lessons in preventing maternal morbidity and mortality - Jain, Manisha; Modi, Jyoti Nath (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The spectrum of causes leading to maternal morbidity and mortality may be well reflected in the clinical profile of obstetric patients admitted to the Intensive Care Unit (ICU). An audit of these patients may help in devising intervention strategies and implementing preventive measures. This is expected to contribute to the ongoing concerted multipronged efforts towards reducing maternal mortality as a step towards the millennium development goals. The aim was to study the clinical and demographic profile of antenatal and postpartum women requiring admission to the ICU, the interventions required in these women and the final outcome. The overall goal is to identify the contributing factors towards maternal morbidity and mortality. Methods: A retrospective analysis of hospital records of all antenatal, post-abortal and postpartum women admitted to the ICU at People’s hospital, Bhopal over a period of 3 years (June 2011 to May 2014). Results: A total of 157 records were identified and analyzed: 22 (14%) antenatal, seven (4%) post-abortion, 114 (73%) postpartum, and 14(9%) post-laparotomy women. The mean age was 25 years (Range 18-38 years; SD 4.49), two thirds being from rural areas. Majority (78%) had no earlier visit. The gestational age at admission to ICU ranged from 6-43 weeks (Mean 31 weeks; SD 9.06). One third (24%) of patients had severe anemia, 18 patients needed ventilation, 25 required inotropic support, 4 required dialysis and 17 underwent surgical intervention. Blood or blood component therapy was needed in 60% cases with total blood units transfused being 225. The average duration of stay in intensive care unit was 79 hours. Analyzing as organ-system dysfunctions: Cardiovascular dysfunction (22%), hematological (20%), hepatic (16%), neurological (11%), septicemia (11%), renal (9%). There were 19 maternal deaths. Conclusions: Maternal anemia and consequences still contribute significantly to maternal morbidity. Non-utilization of antenatal care services especially in rural area compounds the problem. Multidisciplinary care is essential in intensive care setting.